UNCOVERING THE SCIENCE MULTILITERACY MODEL AND ITS RELATIONSHIP TO STUDENTS' CRITICAL THINKING SKILLS IN ELEMENTARY SCHOOL: - - Hasanah, Uswatun; -, Edwita; -, Imaningtyas; Januar, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to reveal the role of the multiliteracy model and its influence on critical thinking skills for fifth-grade elementary school students. This study is an experimental study with a research design used in this study, namely Pretest Posttest Control Group Design. The data analysis technique in this study is the T-test. The study results showed that based on the difference test with the independent samples test, it is known that the Sig. (2-tailed) value of 0.00 is smaller than 0.05, thus it can be concluded that there is a significant difference between the average critical thinking skills of students in the experimental class and the group of students in the control class. The results of this study can be a recommendation for elementary school teachers in improving the quality of learning including enhancing their students' critical reasoning.